USE OF ENERGY EFFICIENT TECHNOLOGIES IN THE DEVELOPMENT OF NATIONAL ENERGY EFFICIENCY POLICY - VASYLKIVSKYI, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article is devoted to the study of the methodological foundations for the formation and development of methods for the rational use of energy resources. It is proved that since Ukraine occupies a leading position in terms of energy consumption, the development and implementation of energy-efficient solutions for the domestic economy is a priority. The leading world practices of energy efficiency of the economy at each stage of the life cycle are considered and analyzed, which allow identifying existing ways to build energy efficient industrial production. The author of the article concludes that the most important component of the vector of development of energy efficient production is the construction of competent strategic and operational management, the desire to create a unified technical policy common to all participants in the production process at every stage - from design to maintenance and repair. The best ways to achieve such a policy are related to the use of innovative digital models and compliance with the principles of lean management. The analysis of the described methods makes it possible to identify the existing shortcomings and problems of using these methods in the domestic industrial sector, as well as the existing ways to solve them. This will improve the approach to energy efficient production and take into account the use of energy efficient solutions at each stage of the production life cycle. It is determined that this will lead to an increase in the competitiveness of the domestic manufacturing segment in the world community. It is substantiated that legal support for energy efficiency is one of the key elements of Ukraine’s national policy, which contributes to the development of the economy, increase of its competitiveness and sustainability. It is determined that the Law of Ukraine "On Energy Efficiency" is fundamental in regulating energy efficiency relations in Ukraine. It defines the rights and obligations of entities in this area, establishes key terms, sets standards for energy efficiency in various sectors of the economy, and provides for state support instruments. The legislative framework aimed at modernizing and optimizing the energy sector forms the basis for further integration into the European energy space, which will allow Ukraine to gain additional opportunities for the development and stabilization of the energy sector.